2012
DOI: 10.1128/jcm.00345-12
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bacterial Pathogens in Ascitic Fluids from Patients with Suspected Spontaneous Bacterial Peritonitis by Use of Broad-Range PCR (16S PCR) Coupled with High-Resolution Melt Analysis

Abstract: bSpontaneous bacterial peritonitis (SBP) can be a severe complication occurring in patients with cirrhosis and ascites, with associated mortality often as high as 40%. Traditional diagnostics for SBP rely on culture techniques for proper diagnosis, although recent reports suggest that the presence of bacterial DNA in peritoneal fluid in patients with cirrhosis and ascites is an indicator of SBP. A previously published broad-range PCR (16S PCR) coupled with high-resolution melt analysis (HRMA) was compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 28 publications
3
34
0
2
Order By: Relevance
“…However, recent studies using 16S rRNA-based fingerprinting analyses have shown that ascites may also be polymicrobial (10,11) and that the bacterial spectrum is broader than that previously reported in context with SBP (11).…”
mentioning
confidence: 59%
“…However, recent studies using 16S rRNA-based fingerprinting analyses have shown that ascites may also be polymicrobial (10,11) and that the bacterial spectrum is broader than that previously reported in context with SBP (11).…”
mentioning
confidence: 59%
“…Different methods result in a broad variability in detected AF bactDNA ranging from around 10% (18,27,28) with single-plex or multiplex PCR, 30-40% with 16s rRNA PCR (7,13,14,16,21), up to 60% with realtime TaqMan PCR (26), which is well comparable to the prevalence of AF bactDNA in our study cohort. Although the results obtained by some techniques support the traditional concept of monomicrobial BT present in serum and AF (7,13,14,16,21), more recent studies using 16S rRNA-based fingerprinting analyses rather suggest polymicrobial peritoneal diversity questioning this canonical concept (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 80%
“…Prior to PCR analysis, all samples were centrifuged at 8000 rpm for 10 minutes to separate DNA from intact bacterial cells. The supernatant was used for reference standard PCR analysis using a previously described 16 S real-time PCR assay (2227). Briefly, each PCR reaction was performed in a total volume of 50 µL, utilizing 30 µL of PCR master mix and 20 µL of sample.…”
Section: Methodsmentioning
confidence: 99%